El Excentrico, 1967-02-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
February 20, 1967 [20 de febrero de 1967]. No volume or issue number. Cover has of the hosting committee of the 20th Annual United Food Drive. The Talent Show took placeat the Azteca Hall on February 24th and the Dance took place at the I.E.S. Hall on February 26th. Admission price was donation of money or food cans.